Public deliberation and the fact of expertise: making experts accountable. (4th May 2017) - Holst, Cathrine; Molander, Anders
Abstract: This paper discusses the conditions for legitimate expert arrangements within a democratic order and from a deliberative systems approach. It is argued that standard objections against the political role of experts are flawed or ill-conceived. The problem that confronts us instead is primarily one of truth-sensitive institutional design: Which mechanisms can contribute to ensuring that experts are really experts and that they use their competencies in the right way? The paper outlines a set of such mechanisms. However, the challenge exceeds that of producing epistemically optimal expert deliberations because a deliberative political system must also fulfil the ethical and democratic requirements of respect and inclusion. Yet, epistemic concerns justify expertise arrangements in the first place, and measures taken to make the use of expertise compatible with these requirements have to balance the potential rewards from expertise against potential deliberative costs. In the final part of the paper, the regulatory framework of a best practice expert advice system is tentatively analysed to illustrate the applicability and critical potential of our approach.